1999
DOI: 10.2500/105065899781329629
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Enophthalmos: The Silent Sinus Syndrome

Abstract: Although uncommon, enophthalmos may be a presenting symptom of chronic maxillary sinusitis with secondary attentuation of the orbital floor. As such, as awareness of this entity, known as the "silent sinus syndrome," is important to all practising otolaryngologists. Two such cases are presented herein, together with a discussion of the pathophysiology, management, and current literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 15 publications
(3 reference statements)
1
32
0
2
Order By: Relevance
“…Narrow infundibulum and atelectiatic opacified right maxillary sinus are also seen. obstruction results in reduced aeration of the antrum, causing negative sinus pressure and atelectasis [1,3]. Supporting this hypothesis, in our case there is uncinate process being opposed to the inferomedial orbital rim [white arrow in coronal Fig-1] occluding the ostia of right ostiomeatal complex.…”
Section: Discussionsupporting
confidence: 69%
“…Narrow infundibulum and atelectiatic opacified right maxillary sinus are also seen. obstruction results in reduced aeration of the antrum, causing negative sinus pressure and atelectasis [1,3]. Supporting this hypothesis, in our case there is uncinate process being opposed to the inferomedial orbital rim [white arrow in coronal Fig-1] occluding the ostia of right ostiomeatal complex.…”
Section: Discussionsupporting
confidence: 69%
“…The silent sinus syndrome is thinning of the bony floor of the orbit, with resultant enophthalmos in otherwise asymptomatic maxillary sinus disease [3,4]. These cases are frequently associated with maxillary sinus hypoplasia, but normal sinuses demonstrated by normal sinus CT scans have been reported in patients years before development of enophthalmos [5].…”
Section: Silent Sinus Syndromementioning
confidence: 99%
“…Several authors, however, have suggested that chronic negative pressure within the maxillary sinus resulting from sinus ostial obstruction is the cause [2][3][4][5][6][7][8][9]. Subsequent regional bony remodeling is then felt to result in enophthalmos.…”
Section: Pathophysiologymentioning
confidence: 98%